2014
DOI: 10.1002/prs.11670
|View full text |Cite
|
Sign up to set email alerts
|

Explosion and flame characteristics of methane/air mixtures in a large‐scale vessel

Abstract: In this study, experiments of explosions and flame characteristics in methane/air mixtures are performed in a 10-m 3 vessel. Pressure gauges and a high-speed camera are utilized to record the pressure trajectories and the flame propagation process of ignition growth. The experimental results show that the maximum value of overpressure and the maximum rate of the explosion pressure rise are 0.596 MPa and 1.82 MPa/s for the methane (9.5% in volume)/air mixture at atmospheric conditions, respectively. Both values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 44 publications
(42 reference statements)
1
12
0
Order By: Relevance
“…It is noteworthy that the flammability limits for the CH 4 -air mixture obtained in this study agree well with the result published in a previous study (4.9% and 15.9%) [42]. For the DME-air mixture, Mogi et al [43] reported that the flammability limits were 4% and 13% obtained using an explosion vessel with an internal volume of 180 L. A noticeable discrepancy is thus found on the rich limit, and the size of the chamber appears to be an influencing factor on the flammability limits, as argued by Zhang et al [44]. This difference may be explained by the fact that in the small-scale apparatus, acoustic disturbance reflected from the chamber wall may generate turbulent fluctuations facilitating the flame propagation, hence prolonging the explosion limit.…”
Section: Flammability Limitssupporting
confidence: 87%
“…It is noteworthy that the flammability limits for the CH 4 -air mixture obtained in this study agree well with the result published in a previous study (4.9% and 15.9%) [42]. For the DME-air mixture, Mogi et al [43] reported that the flammability limits were 4% and 13% obtained using an explosion vessel with an internal volume of 180 L. A noticeable discrepancy is thus found on the rich limit, and the size of the chamber appears to be an influencing factor on the flammability limits, as argued by Zhang et al [44]. This difference may be explained by the fact that in the small-scale apparatus, acoustic disturbance reflected from the chamber wall may generate turbulent fluctuations facilitating the flame propagation, hence prolonging the explosion limit.…”
Section: Flammability Limitssupporting
confidence: 87%
“…When the gas mixture enters the relatively narrow pipeline, pressure waves develop causing a pressure increase (as seen from the solid lines in Figures and ). A wide, low velocity pressure wave will change into a narrow, fast pressure wave when it encounters a constriction, along with some energy loss . During the explosion process, the pressure wave in both the vessel and in the pipeline encounter the reflected wave from the other side, causing the waves to oscillate back and forth.…”
Section: Resultsmentioning
confidence: 99%
“…High-voltage electric spark was used to supply ignition energy as in previous studies [39][40][41][42][43][44][45][46]. The igniter was mounted at the center of the spherical bomb and a spark energy of 10 J, estimated from 1/2 CU 2 (''C'' and ''U'' refer the capacitance and voltage, respectively.…”
Section: Methodsmentioning
confidence: 99%